Redesain Presiden Berhalangan Sementara Dalam Lembaga Kepresidenan - Muhamad Riziq Maulana; Rizki Maulana Syafei; Muh Zikril; Risma Ridhani Istiqomah (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
In a presidential system, the president plays a key role as both head of state and head of government, making the position crucial in governance. Therefore, a vacancy in the presidency whether temporary or permanent should not occur, even briefly. However, Indonesian law only regulates permanent incapacity and does not address temporary incapacity, creating a legal vacuum. This study aims to formulate a legal concept to regulate the temporary incapacity of the president. The research uses normative legal analysis with conceptual, historical, and comparative approaches, analyzed through the theory of mandate authority. The findings show that the lack of legal provisions for temporary presidential incapacity can disrupt government functions and undermine the rule of law. This gap exists in both normal situations (leave, minor illness, travel) and abnormal conditions (emergencies, serious health issues), where delegation of duties is left to administrative practices. Therefore, a Presidential Institution Law is needed to clearly define the delegation of presidential duties. This law should distinguish between administrative delegation in normal situations and limited delegation of substantive authority in abnormal situations through a mandate mechanism.